A trans-contextual model of motivation in physical education - Barkoukis, V.; Hagger, Martin (Nova Science Publishers, Inc., 2012)
The trans-contextual model of motivation has been developed to describe and explain the motivational processes by which motivation from one context can be transferred to another. The model comprises an integration of self-determination theory, the hierarchical model of intrinsic and extrinsic motivation, and the theory of planned behaviour. This chapter reviews the rationale for integrating these theories into the transcontextual model and outlines recent developments in research using the model. Empirical data from the application of the trans-contextual model in the context of physical education are presented. These data provide support for the model's assumptions and highlight the efficacy of the model to describe the mechanisms by which support for autonomous motivation and motivational regulations in educational contexts (e.g., physical education) can lead to motivation in other contexts (e.g., leisure time physical activity). Finally, avenues for future research on the conceptual and methodological aspects of the model are outlined. © 2012 by Nova Science Publishers, Inc. All rights reserved.